Sportmedizin im Wandel - Thiel A; Schubring A; Schneider S; Zipfel S; Mayer J (Dynamic Media Sales Verlag, 2015)
Background: In the medical practice of elite sports, health, injury, and illness are mostly handled from an exclusively biomedical perspective. However, research has shown that dealing with health in elite sports is strongly influenced by a so called culture of risk. Athletes are willing to take extreme health risks in order to be successful in important competitions, and they find themselves in a permanent action dilemma between the necessity of risking and securing their own health at the same time. Our paper emphasises the importance of integrating psychological and social factors into health management strategies in elite sport.Method: The article is based on data from the German Young Olympic Athletes Lifestyle and Health Management Study (GOAL Study). This nationwide mixed-method study combines quantitative and qualitative approaches in order to gather a broad range of representative information on squad athletes from all Olympic disciplines as well as in-depth information on selected Olympic disciplines. Results: Injuries and pain are everyday epiphenomena of elite sports, already at young age. In many cases, injuries are the result of a complex interplay of biological, psychological and social processes. Athletes are used to train and compete under constant suffering of pain. In order to fulfil sports specific expectations they develop behavioural patterns that outside the context of elite sports would be characterised as harmful. The process of internalising these patterns already starts in adolescence. Coaches play an important role in this process. Athletes implicitly learn to partly give up their individual pain sensorium.KEY WORDS: Health in Elite Sports, Sports Injuries, Biopsychosocial Perspective, Psychosocial Factors